MANAGEMENT OF STRUVITE UROLITHIASIS IN AN AMERICAN BULLY DOG - Yennifer; Sri Kayati Widyastuti; I Gusti Made Krisna Erawan (Buletin Veteriner Udayana, 2026)
Urolithiasis is one of the most common urinary tract disorders in dogs and can be influenced by nutritional factors, breed, sex, water intake, and infections caused by urease-producing bacteria. This article reports a 4-year-old female American Bully dog presenting with intermittent hematuria for eight months. Urinalysis revealed an alkaline urine pH of 8, urine specific gravity ≤ 1.010, and a very high number of struvite crystals. Ultrasonographic examination showed hyperechoic sand-like material within the urinary bladder, while no uroliths were detected on radiographic examination. Hematological and serum biochemical analyses revealed mild changes that remained within physiological limits. The therapeutic approach included administration of cefadroxil, methylprednisolone, Cystaid®, Nutri-Plus Gel®, and dietary modification to a therapeutic Urinary S/O for 14 days. Clinical and ultrasonographic evaluations after therapy demonstrated a reduction in the number of bladder crystals, along with improvement in urine color and odor. This case highlights that a combination of pharmacological therapy and dietary management plays an important role in the treatment of struvite urolithiasis in dogs, particularly cases associated with uncontrolled dietary patterns.